Implementation of POP-UP Book in Supporting Literacy at SD Negeri 1 Tataaran - Norma Monigir; Amalia Poli (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This research is motivated by the importance of improving literacy culture among elementary school students through innovative and engaging learning media. Learning media is a tool that helps teachers convey learning materials in such a way that they make students interested and interested in the learning materials presented. Using learning media dramatically improves the learning process's efficiency and the delivery of messages and the content of learning materials. Media reinforces learning process activities with different characteristics and must be carefully selected to be used effectively. The right learning media is critical in supporting learning for students. This study uses a qualitative research method with a case study approach. This research focuses on SDN 1 Tataaran, one of the schools where PPL Pre-service PPG students are located. At the school, the class that is the place of observation has implemented pop-up book media. A four-week observation showed that pop-up books were a supporting medium in group and individual reading sessions. Interviews with students revealed they were more interested in reading when using pop-up books than regular textbooks. Most students admitted to feeling happy with the visual appearance and interactivity offered by the pop-up book. The study's conclusion shows that pop-up books are an effective and innovative learning medium. This research has made a significant contribution to the field of education, showing that interactive media such as pop-up books can improve various aspects of children's intelligence in an interesting and fun way. For further research, it is recommended that more careful planning is needed in the development of pop-up book media, which should be developed according to the needs and characteristics of students.